Symbiotic N2 Fixation, Leaf Photosynthesis, and Abiotic Stress Tolerance of Native Rhizobia Isolated from Soybean Nodules at Da, Upper West Region, Ghana - Mmatladi Tesia Mataboge; Mustapha Mohammed; Felix Dapare Dakora (Microorganisms)
The soybean is an important source of protein and is gaining popularity in Ghana due to a rising demand for its use in the poultry industry. However, the grain yield of soybeans is relatively low in the Upper West Region due to infertile soil and climate change. This study evaluated root nodulation and symbiotic effectiveness in 31 rhizobial isolates obtained from the nodules of soybeans planted at Da in the Upper West Region, Ghana, as well as measured photosynthetic activity of the soybean plants grown under glasshouse conditions. This study further assessed the tolerance of the rhizobial isolates to different levels of temperature, drought, salinity, and pH in the laboratory and also measured the ability of the isolates to produce indole-3-acetic acid. An infrared gas analyser and the 15N and 13C natural abundance techniques were used to assess the photosynthetic activity, N2 fixation, and water-use efficiency, respectively. The results showed that the test isolates that induced greater photosynthetic rates from higher stomatal conductance also stimulated increased water loss via leaf transpiration in soybean plants. Isolates TUTGMGH9 and TUTGMGH19 elicited much higher shoot δ13C in the soybean host plant and induced higher shoot biomass, C accumulation, percent relative symbiotic effectiveness, and N2 fixation relative to Bradyrhizobium strain WB74 and 5 mM of nitrate, which were used as positive controls. Although isolate TUTGMGH9 did not grow at 40 °C, it showed growth at 5% of PEG-6000, NaCl, and a low pH while also producing moderate IAA. However, for better utilisation of these rhizobial isolates as bioinoculants, their growth performance needs to be assessed under field conditions to ascertain their competitiveness and symbiotic efficacy.